Cognições de professores sobre pesquisas relacionadas ao processo de ensino e aprendizagem de LE um estudo Q - Silva, Lauro Luiz Pereira (2012)
This work is linked to the group that develops research on subjective aspects of foreign language teaching and learning process at the Instituto de Letras e Linguística of a Federal University. Its main objective is to investigate cognitions, conceptions and points of view about the role and relevance of research for in-service English language teachers and for professors / researchers working with language teachers` education. The term cognitions , according to Borg (2003) refers to non-observable aspects of the cognitive dimension: what the teachers know, believe and think. Thus, the development of the research starts from the following questions: (a) What are the cognitions of regular public school foreign language teachers` about research developed by professors working with language teachers` education? (b) What are the cognitions of professors working with language teachers` education, about research developed in/about the regular school context? To which extent do participants` cognitions converge / diverge? Q Methodology research approach, which makes use of PQMethod 2.11 software, was used. Focal group and semi-structured interviews were used, as secondary data gathering tools, for raising a wide range of participants` points o view and subsequent composition of a semi-structured Q sample of statements. These represent the participants` cognitions about the role and contributions of research on the process of teaching and learning foreign language. The subjects distributed statements along a continuum in a scale ranging from Totally agree (+5) to Totally disagree (-5), and the results of the Q Distribution were analysed with PQMethod 2.11 software. From further qualitative and interpretive analysis, the factors, or groups, that emerged from the fator analysis were defined, characterized and interpreted. These groups of participants share similar points of view about research on the teaching and learning process. The following aspects stand out among the emerging results: the relationship between theory and practice, Applied Linguistics contributions to foreign language teachers` Education, foreign language reflective practice, teachers and professors` cognitions about the relevance of research to practice; and the (re)construction of teacher knowledge in Applied Linguistics research. I believe that, through the development of awareness of roles and critical stance of practices, the results of this research may bring contributions to foreign language teachers at regular public schools as well as to professors working with language teachers` education.